FATAL TRANSFUSION-ASSOCIATED GRAFT-VERSUS-HOST DISEASE IN THE PATIENT AFTER AORTOCORONARY BYPASS (Clinical case) - O. V. Goloschapov; M. A. Estrina; N. E. Ivanova; I. M. Barkhatov; A. D. Kulagin; S. N. Bondarenko; I. S. Moiseev; I. V. Shlyk; Yu. S. Polushin; B. V. Afanasiev (Вестник анестезиологии и реаниматологии, 2018)
Goal: to demonstrate the rare case of transfusion-associated graft-versus-host disease (TA-GvHD) after transfusion of blood components. The cause of TA-GvHD is implantation of donor lymphocytes, contained in blood components, which is related to immunological HLA-homology between the donor and recipient, that does not eliminate the donor cells. Mortality makes 90-100%. 68 year old patient had planned surgery - aortocoronary bypass. In the post-operative period under pressure anemia three doses of unirradiated packed red blood cells were transfused. On the 17th day after transfusion the patient developed febrile fever and manifested erythematous cutaneous rush. On the 24th day after transfusion neutropenia developed. Evaluation results of allele discrimination of high-polymorphic markers confirmed the diagnosis of TA-GvHD. HLA-typing of the donor's and recipient's blood was done retrospectively. The donor was homozygous in five loci in low resolution and in loci of HLA-А*, HLA-В*, HLA-DRB1* he had the gene common with the patient. On the 34th day after the transfusion the patient died of infectious complications. X-ray or gamma-irradiation of blood components in order to inactivate the donor's viable T-lymphocytes is considered to be the only way to guarantee the prevention of TA-GvHD. Since there is no effective therapy for TA-GvHD, prevention of risk to develop the disease, strict indications to blood transfusions and capacity for early diagnosis become crucial.